2020
DOI: 10.21203/rs.3.rs-89184/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relationship between smartphone usage duration (using smartphone’s ability to monitor screen time) with hand-grip and pinch-grip strength among young people. An observational study

Abstract: BackgroundThe use of smartphones has become widely popular especially among young people for multiple purposes other than communication including gaming and internet browsing. The weakness of the hand and wrist is one of the main complications associated with the increase of use of smartphones. This weakness occurs due to the repetitive flexion and extension of the wrist, thumb and fingers which eventually could lead to a major musculoskeletal pathology. Little is known about the relationship between smartphon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…The association between smartphone usage duration (as measured by the phone's capacity to track screen time) and hand-grip are incompletely defined. As a result, a link between smartphone usage duration as well as hand-grip strength in young adults was investigated in which the long-term smartphone use was linked to a weaker grip grasp and the length of time spent on a smartphone, as well as age which may play a role in the strength of the hand muscles [17]. The grip strength in healthy young Indians was assessed using data from 1005 healthy volunteers with a mean age of 22 years for both males and females demonstrating that the least age limit was chosen at 18 years to allow for musculoskeletal maturity, while the maximum age limit was set at 30 years to account for the increasing loss of functional independence [9].…”
Section: Reviewmentioning
confidence: 99%
“…The association between smartphone usage duration (as measured by the phone's capacity to track screen time) and hand-grip are incompletely defined. As a result, a link between smartphone usage duration as well as hand-grip strength in young adults was investigated in which the long-term smartphone use was linked to a weaker grip grasp and the length of time spent on a smartphone, as well as age which may play a role in the strength of the hand muscles [17]. The grip strength in healthy young Indians was assessed using data from 1005 healthy volunteers with a mean age of 22 years for both males and females demonstrating that the least age limit was chosen at 18 years to allow for musculoskeletal maturity, while the maximum age limit was set at 30 years to account for the increasing loss of functional independence [9].…”
Section: Reviewmentioning
confidence: 99%
“…It also causes hand and thumb pain with reduced handgrip strength, and upper limb functions at the workplace. 9 The incidence of these symptoms is 3.8%, while the prevalence rate in females is 9.2% and in males it is 6%. 10 A number of studies showed that handgrip strength was inversely related to functional impairments,…”
Section: Introductionmentioning
confidence: 98%
“…Osailan evaluated the association among smartphone use (in time units) along with hand-grip strength among youthful individuals. It was found out that in comparison to lower frequency smartphone users, greater frequency smartphone users reported weaker handgrip strength (9). Gripping, continuous pushing movements along with repeated thumb motions, Despite, were all risk factors for upper-limb dysfunction (6).…”
Section: Introductionmentioning
confidence: 99%
“…Dry eyes, computer vision complication, neck as well as shoulder issues, De Quervain's tenosynovitis, and thumb and wrist weakness are some of the complications along with negative effects of prolonged smartphone use. These challenges would reduce the hand's functionality over time, potentially leading to psychological issues resulting in low quality of life (9). The use of the internet has become excessive among youths and adults all over the world.…”
Section: Introductionmentioning
confidence: 99%